Sustainable Management and Conservation of Drinking Water Resources in Himalayas - Bisht, N. S.; Srivastava, A. C. (Indian Forester, 1995)
Scarcity of water has become a regular feature in most of our cities. The ground water table is going deeper day by day becauase we are ignoring the natural ways (in situ methods) of storing water. An attempt has been made to highlight the problem of drinking water in U.P. hills along with some measures to conserve and utilise these resources on sustainable basis.